2002
DOI: 10.1126/science.1072104
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Shotgun Assembly and Analysis of the Genome of Fugu rubripes

Abstract: The compact genome of Fugu rubripes has been sequenced to over 95% coverage, and more than 80% of the assembly is in multigene-sized scaffolds. In this 365-megabase vertebrate genome, repetitive DNA accounts for less than one-sixth of the sequence, and gene loci occupy about one-third of the genome. As with the human genome, gene loci are not evenly distributed, but are clustered into sparse and dense regions. Some "giant" genes were observed that had average coding sequence sizes but were spread over genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
1,010
5
8

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,446 publications
(1,058 citation statements)
references
References 60 publications
35
1,010
5
8
Order By: Relevance
“…It seems difficult to understand how the chromosomes of 3nCC performed pairing during meiosis. Considering the fish-specific genome duplication that was regarded as having happened in the history of teleosts evolution [17-20], 3nCC could actually be regarded as an ancient hexaploid which could certainly perform pairing of homologous chromosomes during meiosis. Therefore, the results supported the occurrence of genome duplication in fish evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems difficult to understand how the chromosomes of 3nCC performed pairing during meiosis. Considering the fish-specific genome duplication that was regarded as having happened in the history of teleosts evolution [17-20], 3nCC could actually be regarded as an ancient hexaploid which could certainly perform pairing of homologous chromosomes during meiosis. Therefore, the results supported the occurrence of genome duplication in fish evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on comparative genomics have further suggested that the third round of fish-specific genome duplication might have occurred in ray-finned (actinopterygian) fishes about 350 million years ago during the divergence between teleost fish and basal actinopterygian lineages. Polyploidy induces redundant genes, increasing the possibility of gene loss, gene silencing, subfunctionalization of genes, and evolution to new genes [17-21]. These variations provide polyploids with more possibilities for new characteristics and adaptations than diploids.…”
Section: Introductionmentioning
confidence: 99%
“…A whole-genome shotgun assembly of the genome of Takifugu rubripes was published recently [2]. Blast searches of the known Hox-A proteins from other species against version 3.0 of the Fugu database [34] leave little doubt that there are two Hox-A clusters.…”
Section: Methodsmentioning
confidence: 99%
“…With the complete sequencing of the pufferfish genome, we can predict that studies into the proteomes of other fishes will capitalize on these sequence resources by using sequence similarity search methods [59]. Once a bird's or reptile's genome is sequenced, we can expect to see developments in the proteomics of related organisms.…”
Section: Perspective: Proteomics and Phylogenetic Considerations For mentioning
confidence: 99%